INFLUENCE OF SOWING PERIODS ON THE FORMATION OF YIELD OF SUNFLOWER HYBRIDS - Марініч, Любов; Неводничий, Ярослав (SWorldJournal, 2024)
Topicality. One of the main tasks at the current stage of the development of agricultural production is to increase the gross harvest of sunflower without expanding its sown areas, but at the expense of increasing the yield of sunflower by improving the e